Transcutaneous Vagus Nerve Stimulation (tVNS) for Treatment of Drug-Resistant Epilepsy: A Randomized, Double-Blind Clinical Trial (cMPsE02) - Bauer, S.; Baier, H.; Baumgartner, C.; Bohlmann, K.; Fauser, S.; Graf, Wolfgang; Hillenbrand, B.; Hirsch, M.; Last, C.; Lerche, H.; Mayer, T.; Schulze-Bonhage, A.; et al. (Brain Stimulation, 2016)
Various brain stimulation techniques are in use to treat epilepsy. These methods usually require surgical implantation procedures. Transcutaneous vagus nerve stimulation (tVNS) is a non-invasive technique to stimulate the left auricular branch of the vagus nerve at the ear conch.We performed a randomized, double-blind controlled trial (cMPsE02) to assess efficacy and safety of tVNS vs. control stimulation in patients with drug-resistant epilepsy.Primary objective was to demonstrate superiority of add-on therapy with tVNS (stimulation frequency 25 Hz, n = 39) versus active control (1 Hz, n = 37) in reducing seizure frequency over 20 weeks. Secondary objectives comprised reduction in seizure frequency from baseline to end of treatment, subgroup analyses and safety evaluation.Treatment adherence was 84% in the 1 Hz group and 88% in the 25 Hz group, respectively. Stimulation intensity significantly differed between the 1 Hz group (1.02 ± 0.83 mA) and the 25 Hz group (0.50 ± 0.47 mA; p = 0.006). Mean seizure reduction per 28 days at end of treatment was -2.9% in the 1 Hz group and 23.4% in the 25 Hz group (p = 0.146). In contrast to controls, we found a significant reduction in seizure frequency in patients of the 25 Hz group who completed the full treatment period (20 weeks; n = 26, 34.2%, p = 0.034). Responder rates (25%, 50%) were similar in both groups. Subgroup analyses for seizure type and baseline seizure frequency revealed no significant differences. Adverse events were usually mild or moderate and comprised headache, ear pain, application site erythema, vertigo, fatigue, and nausea. Four serious adverse events were reported including one sudden unexplained death in epilepsy patients (SUDEP) in the 1 Hz group which was assessed as not treatment-related.tVNS had a high treatment adherence and was well tolerated. Superiority of 25 Hz tVNS over 1 Hz tVNS could not be proven in this relatively small study, which might be attributed to the higher stimulation intensity in the control group. Efficacy data revealed results that justify further trials with larger patient numbers and longer observation periods.
EVALuna2:22447